Registration and assessment of load cycles in pipelines - Torop, O.; Schmidt, V. (Проблемы прочности, 2009)
An optimized load cycle registration and assessment method was developed on the basis of evaluation of the fatigue test series with arched test pieces. The tests were performed under Wohler-type and transient loading conditions. Test results were evaluated using different load cycle registration and assessment methods. The finite-element simulations were performed, in order to verify the systematical and random errors caused by the chosen test setup and of the test specimen geometry. Розроблено оптимізованнй метод реєстрації й оцінки циклів навантаження, який базується на аналізі результатів утомних випробувань зразків у вигляді арки. Випробування проводили за постійних (за типом побудови кривих утоми) та змінних амплітуд циклічних напружень. Виконано скінченноелементні розрахунки, що дозволяє оцінити рівень систематичних і випадкових похибок, зумовлених схемами утомних випробувань та геометрією зразків, що використовуються. Разработан оптимизированный метод регистрации и оценки циклов нагружения, основанный на анализе результатов усталостных испытаний образцов в виде арки. Испытания проводили при постоянных (по типу построения усталостных кривых) и переменных амплитудах циклических напряжений. Выполнены конечноэлементные расчеты, позволяющие оценить уровень систематических и случайных погрешностей, что обусловлено используемыми схемами усталостных испытаний и геометрией образцов.